Impact of Traffic Congestion: Case Study of Jatiwangi-Majalengka Highway Section - Agus Wirdianto; Muhamad Taufik; Jody Martin Ginting (Fakultas Teknik Sipil dan Perencanaan, 2025)
Traffic congestion is a common problem that plagues most metropolitan cities in the world. In Indonesia, traffic jams have become part of the daily routine, especially in big cities like Jakarta (Indonesia), Mumbai (India), and New York (United StatesHighways experience significant congestion during peak hours, which generally occur twice a day, in the evening and also in the morning. This is usually caused by the work schedule of workers who leave in the morning and return in the afternoon. It is this concentration of vehicles at peak hours that triggers congestion. There are also other factors associated with congestion, such as the lack of adequate public transportation alternatives, so that people prefer to use private vehicles. Thus, collaborative efforts from various parties are needed to address this issue as a whole. And usually vehicles such as cars, and motorcycles park carelessly, as well as street vendors who like to sell on the side of the road which is the impact of the congestion that often occurs. The purpose of this paper is to adopt a qualitative approach to assess the impact of congestion related to road speed and density. This research method was carried out by survey on the Bandung-Palimanan road, Ciborelang village, Jatiwangi sub-district, Majalengka district in December 2024 which has a length of about ± 200 meters. Data analysis using primary data consisting of the number of vehicles passing, Microsoft Excel 2013 and Traffic Counter software The results revealed that the volume of vehicles peaked at 2543.4 vehicle units per hour, which indicates the occurrence of traffic congestion, with the highest speed reaching 66.92 km / h, which identifies that conducive traffic conditions allow transportation to move at a fairly high speed.